2021
DOI: 10.1245/s10434-021-09649-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes After Surgical Resection of Pancreatic Metastases from Renal Clear-Cell Carcinoma

Abstract: Background Pancreatic metastases (PM) from renal cell carcinoma (RCC) are uncommon. We herein describe the long-term outcomes associated with pancreatectomy at two academic institutions, with a specific focus on 10-year survival. Methods This investigation was limited to patients undergoing pancreatectomy for PM between 2000 and 2008 at the University of Verona and Memorial Sloan Kettering Cancer Center, allowing a potential for 10 years of surveillance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…The type of surgery performed varied widely depending on the location of the tumor, with PD being the one seen more often. Atypical resection was performed in just 5 patients (4.3%), which differs from other studies in which this rate has been higher [19,20].…”
Section: J O U R N a L P R E -P R O O Fcontrasting
confidence: 73%
See 3 more Smart Citations
“…The type of surgery performed varied widely depending on the location of the tumor, with PD being the one seen more often. Atypical resection was performed in just 5 patients (4.3%), which differs from other studies in which this rate has been higher [19,20].…”
Section: J O U R N a L P R E -P R O O Fcontrasting
confidence: 73%
“…The medical literature on pancreatic resection due to metastasis is limited to isolated cases or retrospective series. However, in select patients, there seems to be a benefit to survival when they undergo surgery, especially in cases where RCC is the primary tumor [3,7,[19][20][21]. However, in select patients, there seems to be a benefit to survival when they undergo surgery, especially in cases where RCC is the primary tumor [3,7,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to OS, patients with pancreatic metastases fared better than mRCC patients with other metastases (median OS 38.4 months, 95% CI, 18.4-72.0 vs. 20.1 months, 95% CI, 8.7-41.1, respectively; p < 0.001). Finally, mRCC patients with Complications in pancreatic MTX for mRCC are common, including pancreatic fistula, delayed gastric emptying, postpancreatectomy hemorrhage, intestinal bleeding, acute respiratory distress syndrome and wound infections (80,82,83). Malleo et al reported a morbidity rate of 34.8% (n = 24) (80) and mortality rate was 2.9% (n = 2) in the perioperative period (80,82,83).…”
Section: Pancreasmentioning
confidence: 99%